Pembelajaran Pendidikan Agama Islam di Sekolah Berbasis Pendekatan Culturally - Rafilah, Nabila Hasna; Firdaus, Endis; Fakhruddin, Agus (Institut Agama Islam Darul Fattah Lampung, 2024)
This research aims to examine the application of the Culturally Responsive Teaching (CRT) approach in learning Islamic religious education in schools. CRT is a learning approach that emphasizes recognizing and integrating students' cultural diversity, backgrounds and experiences in the learning process. This study uses qualitative research methods by involving students from various cultural backgrounds and teachers' learning strategies in the learning process. Data was collected through classroom observations during teaching and learning activities and interviews with PAI teachers who implemented CRT. The integration of CRT in PAI learning can help create an inclusive learning environment, promote cross-cultural understanding, improve students' learning abilities and be able to manage the rights of all students in the process. The results of the research are that learning that takes into account students' cultural diversity can create an inclusive learning environment and support the development of strong religious values. This study also provides a more comprehensive view of the importance of recognizing and responding to cultural diversity in the context of religious education, which in turn can improve the quality of education in schools.